Policy Networks: Empirical Evidence and Theoretical Considerations - Bernd Marin; Renate Mayntz (Campus Verlag; Max-Planck-Gesellschaft zur Förderung der Wissenschaften e.V., 1991)
Political governance in modern societies can no longer be conceived in terms of external government control of society but emerges from a plurality of governing agents. In contemporary policy making, governmental and non-governmental actors are interconnected in complex networks of interaction, exchanging information and other resources. This reader presents the results of empirical network studies in a variety of policy sectors and in different countries. It also provides insights into innovative quantitative and qualitative approaches to network analysis.
hdl:11858/00-001M-0000-0012-5B0E-5
Keywords: 300